PENGEMBANGAN BUKU POP-UP MATERI DALHADHAMMA JĀTAKA SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN ANAK USIA DINI: PENGEMBANGAN BUKU POP-UP MATERI DALHADHAMMA JĀTAKA SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN ANAK USIA DINI - Sehati, Sehati; Sukodoyo, Sukodoyo; Waluyo, Waluyo (Jurnal Pencerahan, 2020)
The goal of this research is to know the process of making Pop-up book theory Dalhadhamma Jātaka as lesson media for Early Childhood Education Programs. This research used the research and development methods in four-levels. Based on the research and discussion which have been done, the making of pop-up book theory Dalhadhamma Jātaka consists of steps as follows: (a) analysis, in this step observation and interview were done to state that the teacher needed innovative and interactive lesson media basic on three dimensions to reach developmental aspects. (b) design, the steps were done to determine the theory of story, and moral value to be delivered, and the script composing to be understood by early childhood. (c) development, at this step the researcher, made the illustration corresponding to the storyline by using many techniques on making Pop-up. The product resulting from this process was the two-book series contained being thankful and loving animal's moral value, (d) implementation, the researcher conducted limited trials to thirteen kindergarten students and four kindergarten Buddhist teachers in Semarang Regency (e) evaluation, the evaluation of the product was done in the form of suggestion in the sense of quality product improvement so that it can be long-lasting.